0} \atop {\frac{4-3x}{2}<3}} \right.\\\\ a)\\ \frac{4-3x}{2}>0\\ 4-3x>0\\ -3x>-4\\ x=(-\infty; \frac{4}{3})\\\\ b)\\ \frac{4 -3x}{2}<3\\ 4-3x<6\\ -3x<2\\ x=(-\frac{2}{3}; + \infty)\\ x = (-\frac{2}{3}; \frac{4}{3})" alt="0 < 1 + \frac{2-3x}{2} <3\\\\ 0<\frac{2 + 2 -3x}{2}<3\\\\ \left \{ {{\frac{4-3x}{2}>0} \atop {\frac{4-3x}{2}<3}} \right.\\\\ a)\\ \frac{4-3x}{2}>0\\ 4-3x>0\\ -3x>-4\\ x=(-\infty; \frac{4}{3})\\\\ b)\\ \frac{4 -3x}{2}<3\\ 4-3x<6\\ -3x<2\\ x=(-\frac{2}{3}; + \infty)\\ x = (-\frac{2}{3}; \frac{4}{3})" align="absmiddle" class="latex-formula">